Soil physicochemical properties after establishment of oil palm plantation in peat swamp forests at Mukah, Sarawak - Zulfaqar, bin Sa'adi (2011)
Soil properties determination is important towards an improvement of both strategy and techniques for future development of conversion peat swamp forest into oil palm plantation. This study discusses soil properties of peat swamp forest under oil palm plantation in Kampung Igan, Mukah, Sarawak. in comparison with the sUlTounding peat swamp forests. Peat soil samples in this study were collected from peat swamp forest (PI), Ladang Rakyat Pelita Igan Jaya oil palm plantation for young oil palm plantation of 2 years old (P~) and Felcra Bhd oil palm plantation for mature oil palm plantation of more than 15 years old (P3)) The size of each experimental plot was 20 x 20m. Soil samples were collected at 0-25 cm depths at each site. For P2 and P3, soil samples were collected and differentiate as no fertilizer point and fertilizer point. Undisturbed cores and bulk samples were collected for analysis of bulk density and moisture content. Soil physicochemical properties were determined by standard procedures. The findings showed that PI and P2 classifies as 05gn (peat soil) while P3 was 4fw-05gn (mixed mineral and peat soil). Soil pH, soil bulk density, water content and soil hardness was increased while soil organic matter and soil porosity was decreased. Dry matter content and moisture content show inconsistency between the sites. As the differences between fertilizer point and no fertilizer point in P2 and P3 showed various trend for each analysis. Results of this study will be useful in predicting the soil condition trend between ages ofoil palm plantation in various perspectives and ensure continuous benefits from the development of peat swamp forest especially involving plantation activities and soil management.